Investigación de metabolitos secundarios en plantas medicinales con efecto Hipoglicemiante y determinación del Cromo como factor de tolerancia a la glucosa - Castro L., Americo (2002)
The presence of secondary metabolites and of chromium element in seven medicinal plants empirically used for their hypoglycemic action by a phytochemical screening and a qualitative method and other one that is quantitative by Atomic Absorptioli. Spectroscopy for detelmining trivalent chromium has been researched. The studied species are: Phyllantus niruri L. (Chancapiedra), Geranium dielsianum Knut (Pasuchaca), GentianeIla alborosea G. (Hercampure), Otholobium pubescells (Culén), Smallantus sonchifolia (Yacón), Chloraphora tincoria (Mora) y Taraxacum officinalis W (Diente de león). It was phytochemically determined the presence of the following secondary metabolites: alkaloids, flavonoids , tannins, saponins and glycosides, by means of color and precipitation reagents. The determination of chromium element was carried out by qualitative and quantitative via. The accomplished study concludes that, the chemical components determined in the studied species, have a meaning ful importance that can have relationship with their empirical usage of hypoglycemic action.